Nutritive Value of Bekariya (Indigofera Cordifolia) for Camel (Camelus Dromedaril.Ls) - Mathur, C S; Purohit, G R (Annals of Arid Zone, 2016)
A conventional metabolic trial with 6 Bikaneri camels (Camelsis dromedarius) was conducted for the evaluation of the nutritive value of bekariya (Indigofera cordifolia) fodder. The average daily dry matter intake of the fodder was 2.08Â±0.02 kg for 100 kg body weight. The digestibility coefficients of various nutrients were: D.M. 60.95 Â±2.50; C.P.66.81Â±1.61: E.E. 70.63Â±0.95; C.F. 49.06Â±1.58; N.F.E.61.65Â± 1.34 and gross energy 63.14Â± 1.0’) Mean daily N, Ca and P balances were: -O.01Â±0.47Â·g; -6.6GÂ±O.05 g; and -0.12Â±2.40 g respectively. The analyses also revealed the following values of applied nutritional importance: D.C.P ., 4.17%; T.D.N., 42.3%; N.R., 1.94 and digestible energy, 20.40 kcal per 100 kg of the feed.